Predictors of Patients' Intentions to Participate in Incident Reporting and Medication Safety. - Davis, R; Vincent, C; Sevdalis, N (2014)
BACKGROUND: To date, there is a paucity of theory-driven research on the likely determinants of patient involvement in safety-relevant behaviors. In particular, very little work has focused on predictors of patient behaviors that do not involve direct interactions with health-care staff. OBJECTIVE: To examine predictors of patients' intentions to engage in 2 safety behaviors: (1) reporting an error to a national reporting system and (2) bringing medicines into hospital. DESIGN: Cross-sectional survey study. PARTICIPANTS: Eighty medical and surgical hospital inpatients aged 18 to 80 years (mean, 48 years) from one inner city London teaching hospital. METHOD: Survey that measured the utility of constructs of the health belief model and theory of planned behavior in predicting patients' intentions to report an error to a national reporting system or to bring their medications into hospital. Data were analyzed using multiple regression analysis. RESULTS: Control beliefs were the strongest predictors of patients' intentions. Normative beliefs were also a strong predictor of intentions to report an error to a national reporting system. The regression model accounted for smaller percentage of the variance in patients' intentions to bring medications into hospital than to report an error to a national reporting system (37% and 48%, respectively). CONCLUSIONS: Interventions aimed at encouraging the participation of patients in promoting their own safety should consider the extent to which patients feel in control and capable of performing the behavior in question; this will help support patients to work with health-care professionals in ensuring safe care.